Biomechanical and Injury Tolerance Analysis of Tibial Movement Under Different Postures and Impact Loads - Lei Liu; Qian Qian; Hengjia Liu; Hongyan Liu; Jong-Chul Park (Applied Sciences)
The lower limbs play an important role in daily human activities. Therefore, a 3D tibial model is constructed, and finite element analysis is performed to investigate the biomechanical characteristics and injury tolerance of lower limb flexion movement. The maximum equivalent stress at 30° flexion was 19.1 MPa and 31.2 MPa in the normal and dynamic eversion positions, respectively, of the knee joint, 1.4 MPa and 1.1 MPa in the medial tibial plateau, and 1.8 MPa and 1.2 MPa in the lateral tibial plateau. The peak contact force was generally approximately 4000 N when different positions of the tibia were impacted. The maximum contact force of the frontal impact was larger than that of the external impact at 4109 N and 3927 N, respectively. The dynamic knee valgus posture and lateral impacts are more likely to cause tibial injury. The findings of this study provide information for the prevention of sports injuries and rehabilitation treatment.